Broadband Planar Magic-T with Marchand Type Power Divider and Balun - Chou, Po-Jung; Lin, Pei-Chieh; Lin, Yun-Wei; Lu, Jhe-Ching; Chang, Chi-Yang (My University, 2014)
A new broadband high-order planar magic-T is proposed in this paper. The magic-T is formed by Marchand type power divider and balun. Exact synthesis method based on S-domain highpass prototype using Richard\'s theorem tits the magic-T with the user-defined specifications. By discussing the characteristic impedance of the common element shared by the balun and divider, the magic-T can be designed to match different output impedance. A high-order magic-T with wide bandwidth about 100% and reflection coefficient of -15dB is designed as an example where a combination of microstrip lines, slotlines, double-sided parallel-strip line (DSPSL) and coplanar striplines is applied. The simulation and measurement results are matched well.
Keywords: Magic-T; planar structure; highpass prototype; synthesis; impedance-transformation